2020
DOI: 10.1016/j.jnutbio.2020.108412
|View full text |Cite
|
Sign up to set email alerts
|

Association between 12α-hydroxylated bile acids and hepatic steatosis in rats fed a high-fat diet

Abstract: High-fat (HF) diet induces hepatic steatosis that is a risk factor for noncommunicable diseases such as obesity, type 2 diabetes, and cardiovascular disease. Previously, we found that HF feeding in rats increases the excretion of fecal bile acids (BAs), specifically 12α-hydroxylated (12αOH) BAs.Although the liver is the metabolic center in our body, the association between hepatic steatosis and 12αOH BAs in HF-fed rats is unclear. Thus, we investigated extensively BA composition in HF-fed rats and evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 53 publications
3
22
1
Order By: Relevance
“…Recently, a study suggested the 12αOH-to-non-12αOH BA ratio was extremely high in NASH patients [ 54 ]. The increased secretion of 12αOH BA may lead to hepatic steatosis by promoting fat absorption and liver Cidea mRNA expression [ 16 ]. The increase in 12αOH BAs had an association with enhancements of liver Cyp7a1 and Cyp8b1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study suggested the 12αOH-to-non-12αOH BA ratio was extremely high in NASH patients [ 54 ]. The increased secretion of 12αOH BA may lead to hepatic steatosis by promoting fat absorption and liver Cidea mRNA expression [ 16 ]. The increase in 12αOH BAs had an association with enhancements of liver Cyp7a1 and Cyp8b1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in 12α-OH BA levels in NASH patients has been identified [ 6 ]. Recent studies have also revealed that higher plasma 12αOH/non-12αOH BA ratios were related to lower insulin sensitivity in humans [ 15 ] and that fecal 12αOH Bas were strongly associated with hepatic steatosis [ 16 ]. Therefore, regulating BA metabolism might be an effective strategy to prevent NAFLD and related disorders [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the causes of lipid metabolism disorders is increased Free Fatty Acids (FFAs) in the blood (24,28,35). Figure 2.…”
Section: Hfd Induces Increase Free Fatty Acids (Ffas)mentioning
confidence: 99%
“…This stimulated the migration of M1 macrophages. M1 macrophages infiltrate adipose tissue and secrete many pro-inflammatory cytokines, including IL-6, IL-12, and tumor necrosis factor-α (TNF-α) (2,35,49). In addition to increasing the activity of M1 macrophages, HFD also decreases the activity of regulatory T cells and macrophages M2, both of which are anti-inflammatory cells (9).…”
Section: High-fat Diet Induces Adipose Tissue Disordersmentioning
confidence: 99%
“…In rat experiments, excessive energy consumption in the form of a high-fat diet enhances the secretion of 12α-hydroxylated (12αOH) bile acid (BA) (6) . In addition, 12αOH BA concentrations in the liver, portal blood, and faeces are associated with hepatic lipid accumulation (7) . Such an association has also been reported between 12αOH BAs and fatty liver index in a clinical study (8) .…”
Section: Introductionmentioning
confidence: 99%